Educação para a dignidade humana: a contribuição de Paulo Freire na atuação do Centro Sócio Educacional Sanitário Madonnina del Grappa - Jair Militão da Silva (EccoS – Revista Científica)
The text presents and analyzes some contributions of Paulo Freire for the development of an Education for the human being dignity. It remembers, yet, some episodes of the presence of Paulo Freire in Brazil and its repercussion in the academic and social Brazilian environment. It evaluates the influence of the educational proposals of Paulo Freire in the organization and development of the works carried through in a school destined to the attendance of children and youngs excluded of the regular system of education, hosted in the Ceará - Brazil.